Beyond Traditional Scientific Training: The Importance of Community and Empowerment for Women in Ecology and Evolutionary Biology - Horner-Devine, M. Claire; Yen, Joyce W.; Mody-Pan, Priti N.; Margherio, Cara; Forde, Samantha (Frontiers in Ecology and Evolution, 2016)
While the biological sciences have achieved gender parity in the undergraduate and graduate career stages, this is not the case at the faculty level. The WEBS (Women Evolving the Biological Sciences) symposia go beyond traditional scientific training and professional development to address factors critical to women’s persistence in faculty careers: community and empowerment. Through a series of panel discussions, personal reflections and skills workshops, WEBS creates a community-based professional development experience and a space for participants to grapple with central issues affecting their scientific careers. Longitudinal qualitative survey data suggest that WEBS bolsters the participants’ confidence and empowerment, in addition to providing concrete skills for addressing a range of issues necessary to navigating scientific careers, leading to increased career satisfaction and career self-efficacy (i.e., the belief in one’s capacity to pursue their chosen career). These results highlight the importance and need for programs and opportunities for women in STEM that go beyond training in scientific skills and traditional professional development to include those that create a sense of community and empowerment.